MARG Sensor Based Position Estimation for Periodic Movements - Nagy, Balázs (Recent Innovations in Mechatronics, 2024)
The research examined the fusion of signals from magnetometer, gyroscope and acceleration sensors (MARG sensor). The focus of the article is the sensor fusion by supervised learning, which is an estimate of the situation based on the parallel processing of different types of measured data in the case of periodic movements. The applicability of the learning algorithms was examined through a practical example of a pendulum.